Factors Relating to Patient Safety Competencies in D3 Nursing Students - Linda, Silvana Evi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research to identify factors related to competency regarding patient safety among D3 nursing students in Jakarta. Methods: This research will use a cross-sectional design. The research will be carried out at the nursing academy in Jakarta. The sample in this study were level 3 D3 nursing students. The questionnaire was used to measure patient safety competency, knowledge and attitudes. Data analysis was carried out using linear regression techniques. Results:  The study reveals that D3 nursing students have a strong patient safety competency score, with a moderate positive correlation between knowledge and competency. Attitudes also play a significant role, with a positive correlation of 91.9%. Age and education influence attitudes, affecting compliance. Conclusions: Attitude variable significantly influences patient safety competency in D3 nursing students, indicating the need for comprehensive research and increased education to enhance clinical safety.